Naked heat (New York : Hyperion, 2010)
When New York's most vicious gossip columnist, Cassidy Towne, is found dead, NYPD Homicide Detective Heat uncovers a gallery of high profile suspects, all with compelling motives for killing the most feared muckraker in Manhattan. Heat's murder investigation is complicated by her surprise reunion with superstar magazine journalist Jameson Rook.
Fictitiously attributed to Richard Castle, a character on the ABC television show, Castle.
Keywords: Women detectives -- New York (State) -- New York -- Fiction; Journalists -- New York (State) -- New York -- Fiction; Man-woman relationships -- Fiction; Murder -- Investigation -- New York (State) -- New York -- Fiction; New York (N.Y.) -- Fiction; Mystery fiction